Desain Stasiun Pengisian Daya Otomatis Tanpa Kabel Menggunakan Metode Resonansi Kopling Magnetik - Nanda Adiva Yusman; Wahyu Agung Pramudito; Soni Prayogi (G-Tech: Jurnal Teknologi Terapan, 2024)
This research aims to design an automatic wireless charging station using the magnetic coupling resonance method. This method was chosen because of its ability to transfer energy efficiently over a certain distance without requiring a physical connection. This design involves main components such as transmitter and receiver coils, as well as supporting electronic circuits which function to regulate the resonant frequency for maximum energy transfer. This charging station prototype was tested to charge electronic devices such as smartphones. Test results show that this system is capable of transferring power with high efficiency over a distance of up to 20 cm, with a power transfer efficiency reaching 50%. System security is also considered by implementing protection against overheating and foreign object detection. Our results show that automated wireless charging stations can be a practical and efficient solution for everyday electronic device charging needs. Further development is recommended to increase the range and efficiency of power transfer as well as integration with various types of electronic devices